Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\Leftrightarrow-\dfrac{9}{46}+\dfrac{108}{46}-\dfrac{93}{23}:\left(\dfrac{13}{4}-\dfrac{5}{3}x\right)=1\)
\(\Leftrightarrow\dfrac{93}{23}:\left(\dfrac{13}{4}-\dfrac{5}{3}x\right)=\dfrac{53}{46}\)
\(\Leftrightarrow-\dfrac{5}{3}x+\dfrac{13}{4}=\dfrac{186}{53}\)
=>-5/3x=55/212
hay x=-33/212
c: \(\Leftrightarrow\dfrac{3}{1\cdot4}+\dfrac{3}{4\cdot7}+...+\dfrac{3}{x\left(x+3\right)}=\dfrac{18}{19}\)
\(\Leftrightarrow1-\dfrac{1}{x+3}=\dfrac{18}{19}\)
=>x+3=19
hay x=16
=>(5/17+12/17)+(-20/31-11/31)-4/9<=x/9<=(-3/7-4/7)+(7/15+8/15)+2/3
=>-4/9<=x/9<=6/9
=>-4<=x<=6
hay \(x\in\left\{-4;-3;-2;-1;0;...;6\right\}\)
a) (\(6\frac{2}{7}.x+\frac{3}{7}\))=-1.\(\frac{11}{5}+\frac{3}{7}\)
(\(6\frac{2}{7}.x+\frac{3}{7}\))=\(\frac{-62}{35}\)
\(\frac{44}{7}.x\)=\(\frac{-62}{35}-\frac{3}{7}\)
\(\frac{44}{7}.x=\frac{-77}{35}\)
x=\(\frac{-77}{35}:\frac{44}{7}\)=\(\frac{539}{1540}\)
\(A=8\frac{4}{17}-\left(2\frac{5}{9}+3\frac{4}{17}\right)\)
\(=8\frac{4}{17}-2\frac{5}{9}-3\frac{4}{17}\)
\(=\left(8\frac{4}{17}-3\frac{4}{17}\right)-2\frac{5}{9}\)
\(=5-2\frac{5}{9}\)
\(=2\frac{4}{9}\)
\(A=8\frac{4}{17}-\left(2\frac{5}{9}+3\frac{4}{17}\right)\)
\(A=8\frac{4}{17}-2\frac{5}{9}-3\frac{4}{17}\)
\(A=8\frac{4}{17}-3\frac{4}{17}-2\frac{5}{9}\)
\(A=5-2\frac{5}{9}\)
\(A=2\frac{4}{9}\)